Ethics in stem cell research (Bangladesh Journal of Bioethics, 2012)
Stem cells have constituted a revolution in regenerative medicine and cancer therapies by providing the possibility of generating multiple therapeutically useful cell types that could be used for treating some of genetic and degenerative disorders. However, human embryonic stem cell research raises few ethical and political controversies because of its involvement in destruction of human embryos. The ethical issues in human embryonic stem cell research encompasses not only with question of the ethics of destroying human embryos, but also with questions about complicity of researchers in destruction of embryos, moral distinction between creating embryos for research purposes and creating them for reproductive ends and the permissibility of cloning human embryos to harvest stem cells. Bangladesh should formulate its own regulations justifying its stand regarding this matter. DOI: http://dx.doi.org/10.3329/bioethics.v3i1.10867 Bangladesh Journal of Bioethics 2012; 3(1):13-18